Investigation of novel cyclic structure in glycoconjugate using a simple model system. (September 2020) - Huang, Wei; Wang, Hanliu Leah; Wang, Mingzhang; Davis, Keith; Xie, Jin; Brown, Paul W.; Kolodziej, Stephen A.; Zou, Qin; Carroll, James A.; Rouse, Jason; Friese, Olga; Jones, Michael
Abstract: Bacterial capsular polysaccharide protein conjugates are a major class of vaccines for preventing severe bacterial infections. The conjugation of a polysaccharide to a carrier protein is critical for inducing adaptive immune response in healthy humans. Due to the high molecular mass and extensive structural heterogeneity of the glycoconjugate, the underlying sugar linkages and polypeptide site selectivity of the conjugation reaction are not well characterized and understood. Here, we report a model conjugation study using a monosaccharide and a synthetic peptide to investigate the fundamental reductive amination chemistry, which is one of the most commonly utilized conjugation strategies for glycoconjugate vaccines. We identified a cyclic tertiary amine linkage as the primary conjugation linkage for monosaccharides containing dialdehydes. Such linkage is previously not well-recognized by the glycoconjugate vaccine field. Our study has provided insights into this commonly used, yet complex conjugation chemistry and will benefit the design of future protein-polysaccharide-based vaccines. Graphical abstract: Image 1 Highlights: Identification of a novel glycoconjugate linkage using a peptide-monosaccharide model system. The concentration of NaIO4 was varied to study monosaccharide oxidation and the impact to the conjugation. Mass spectrometry and 2D NMR were used to fully characterize the presence of the novel cyclic structures.